ANALISIS KOHESI dan KOHEREN PADA WACANA CERPEN KEUTAMAAN SEDEKAH KARYA HABIBURRAHMAN EL SHIRAY - Setya Nugraha, Alfian; Safira, Alfaza (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
this study will analyze cohesion and coherence in short stories entitled the primacy of alms the work of Habiburrahman El Shirazy to find out the use of chesion and coherence in the short stor. In this case cohesion and coherence are one of the important compenents in the formation of a dicourse or text. This study will discuss lexical cohesion and gramaical cohesion and coherent. This research hopes that better writing can be useful for the reader. With that reader can take the mandate conveyed by the author. The menthod of qualitative description is seen in terms of words, phrase sentences or paragraphs. The technique used is to read and take notes.